2021
DOI: 10.34172/ijhpm.2021.82
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of Representations of Inequalities in Childhood Obesity in Australian Health Policy Documents

Abstract: Background: In Australia, childhood obesity follows a socioeconomic gradient whereby children with lower socioeconomic position are disproportionately burdened. To reduce these inequalities in childhood obesity requires a multi-component policy-driven response. Action to address health issues is underpinned by the ways in which they are represented as 'problems' in public policy. This study critically examines representations of inequalities in childhood obesity within Australian health policy documents publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Our previous research supports the notion that government rhetoric is not equity-oriented with respect to addressing population diets in high-income countries (Zorbas et al, 2021 ). We found that equity was only a surface-level consideration in national nutrition policy strategies, with actions focused on changing individual-level behaviours rather than structural drivers of diet-related health inequities (Chung et al, 2021 ; Zorbas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research supports the notion that government rhetoric is not equity-oriented with respect to addressing population diets in high-income countries (Zorbas et al, 2021 ). We found that equity was only a surface-level consideration in national nutrition policy strategies, with actions focused on changing individual-level behaviours rather than structural drivers of diet-related health inequities (Chung et al, 2021 ; Zorbas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Greater London Authority, 2019 ; Saunders et al, 2017 ). Nonetheless, our previous research has shown that national governments do not have the tools or adequate commitment to achieve these public health imperatives (Chung et al, 2021 ; Zorbas et al, 2020a , 2021 ). Equity-oriented policy progress is likely to continue to be hindered by the inadequate representations of the voices and values of those experiencing social and economic exclusion in policy processes, research and advocacy efforts (Browne et al, 2019 ; Centre for Public Impact - A BCG Foundation, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of a diet with a high intake of energy-dense and low nutrient-dense foods is a major risk factor for weight gain, obesity, and associated metabolic and cardiovascular diseases morbidity and mortality [1]. Families with greater socioeconomic disadvantages, such as lower income, lower educational level, or living in socioeconomically disadvantaged neighborhoods, are more likely to have overweight and poorer health outcomes compared to families with less disadvantage [2, 3]. As such, the price and affordability of food are key determinants in the choice of products included in the shopping basket, with people of lower socioeconomic status being the most sensitive to food prices [4].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that this inequality can likely be attributed to differences in social circumstances and opportunities, not biological inevitability, it should be regarded as an inequity. Improving such health inequities is frequently considered a responsibility of government health policy and funding [4]; however, obesity policies in the UK [5] and Australia [6] have been criticized for failing to address inequities.…”
Section: Introductionmentioning
confidence: 99%